High-strength and high-toughness filtering material and production method thereof
Through reasonable proportioning and process processing in refractory materials, the problem of insufficient volume stability and thermal shock resistance in the production of deformed aluminum alloys was solved, and a high-strength and high-toughness filter material was prepared, with excellent non-stick aluminum properties and long lifespan reduces production costs and improves application effects.
Patent Information
- Application Number
- CN202411299080.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
AI Technical Summary
In the production process of deformed aluminum alloys, existing refractory materials have insufficient volume stability and weak thermal shock resistance, which are prone to safety hazards of cracks and aluminum leakage, which cannot meet the development needs of the aluminum melting and casting industry.
The formulation of high-strength and high-toughness filter materials, including quartz powder, fume powder, wollastonite, rosyite, explosion-proof fiber, calcined alumina, magnesium fluoride and calcium aluminate cement, is formed by dry mixing and wet mixing steps. The product and liquid material are combined with stirring and vibration forming, followed by curing and high-temperature firing, controlling the temperature and time, and improving the material's thermal shock resistance, wear resistance and non-stick aluminum properties.
It realizes high toughness and strength filter materials, with good thermal insulation performance, low thermal conductivity and long service life, reducing production costs and improving market application prospects.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, in particular to a high-strength and high-toughness filtering material and a production method thereof. Background Art
[0002] At present, the materials widely used in the production process of deformed aluminum alloys are mainly quartz materials and high-aluminum materials. Quartz materials have good thermal vibration performance and good volume stability, but their thermal insulation performance is inherently insufficient. Alumina powder materials have good wear resistance and compressive strength. Under the condition of long-term contact with aluminum liquid, they have excellent resistance to slag and corundum tumor accumulation growth, but their volume stability is insufficient, their thermal shock resistance is weak, and they are prone to cracks during use, which poses a safety hazard of aluminum leakage. They cannot meet the development trend and needs of the aluminum casting industry. Therefore, a high-strength and high-toughness filter material and its production method are urgently needed to solve the above problems. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned shortcomings and provide a high-strength and high-toughness filter material, comprising a dry main ingredient and a binder; the dry main ingredient comprises 10-18 parts of quartz powder, 1-5 parts of silica fume powder, 12-20 parts of wollastonite, 1-4 parts of andalusite, 0.3-1 parts of explosion-proof fiber, 1-5 parts of calcined alumina, 0.5-2 parts of magnesium fluoride, and 10-15 parts of calcium aluminate cement by weight; the binder comprises silica sol, xanthan gum, pure water and calcium aluminate cement, the silica sol accounts for 18-55% of the total weight of the dry main ingredient, the xanthan gum accounts for 1.8-8.75% of the total weight of the dry main ingredient, the pure water accounts for 5.45-11.25% of the total weight of the dry main ingredient, and the calcium aluminate cement accounts for 18.2-22% of the total weight of the dry main ingredient.
[0004] Preferably, the silica sol density is 1.2 g / cm 3 .
[0005] Preferably, the wollastonite, silica fume powder and quartz powder are 50-140 meshes, and their main function is to reduce thermal conductivity and improve thermal shock resistance and anti-scouring ability of the product.
[0006] Preferably, the calcined alumina is 3000-4000 mesh.
[0007] Preferably, the purified water is 12-18% of the total amount of the silica sol and the xanthan gum.
[0008] Preferably, the silica sol and xanthan gum account for 20-30% of the total amount of the dry main ingredients and the binder.
[0009] The present invention also includes a method for producing a high-strength and high-toughness filter material, comprising the following steps:
[0010] Step 1, dry mixing: firstly, weighed quartz powder, wollastonite, silica fume powder, andalusite, calcium aluminate cement, explosion-proof fiber, calcined alumina, magnesium fluoride (cosolvent) and calcium aluminate cement are put into a mixing device 1, stirred and mixed to form a dry material;
[0011] Step 2, wet mixing: adding weighed silica sol, xanthan gum (thickener), and purified water into the mixing device 2, stirring and mixing to form a liquid material;
[0012] Step 3, add the liquid material in step 2 to the dry material in step 1 and stir to mix; stir evenly without lumps or powder, and control the on-site temperature at 15-35°C;
[0013] Step 4: Forming: Put the mixed materials in step 3 into the mold and vibrate to form a green body; specifically, pour the mixed materials into the mold and vibrate for 10-12 minutes. Inspection standard: Put the spherical clay in the palm of your hand and gently shake it into a cone, which is the ideal state;
[0014] Step 5, curing and firing: curing and firing the green body formed in step 4 to form a product; specifically, removing the mold, scraping off excess clay with a spatula, and then curing and firing;
[0015] Step six, testing: Randomly take three products from step five and conduct strength and non-stick aluminum performance tests. If the tests are qualified, the batch of products is qualified.
[0016] Preferably, the stirring time in step 1 is 40-60 min, the stirring time in step 2 is 30-40 min, and the stirring time in step 3 is 10-12 min.
[0017] Preferably, in step five, the curing time is 72 hours, the curing temperature is 15-35°C, and the firing temperature is 750°C.
[0018] The working principle of the present invention is as follows: the present invention achieves good thermal shock resistance by controlling the amount of quartz material added; increases the strength and density of the material by adding wollastonite and silica fume powder, improves the wettability against aluminum liquid, and adds andalusite to improve its wear resistance and strength; adds calcined alumina to improve the room temperature compressive strength of the material and the corrosion resistance against alkaline slag; adds explosion-proof fiber to increase the mechanical properties of the material and improve the crack resistance of the material; adds calcium aluminate cement to shorten the solidification time and improve the strength of the material.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: the filter material made by the present application has higher toughness and strength, and excellent thermal insulation performance, good non-stick aluminum performance, good thermal vibration performance, higher strength and toughness performance and low thermal conductivity; the material has a long service life, can effectively reduce the customer's production and manufacturing costs, and has good market effects and application prospects in filter materials. DETAILED DESCRIPTION
[0020] The present invention is further described below with reference to specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0021] Example 1
[0022] A high-strength and high-toughness filter material comprises a dry main ingredient and a binder; the dry main ingredient comprises, by weight, 10 parts of quartz powder, 1 part of silica fume powder, 12 parts of wollastonite, 1 part of andalusite, 0.3 parts of explosion-proof fiber, 1 part of calcined alumina, 0.5 parts of magnesium fluoride, and 10 parts of calcium aluminate cement; the binder comprises silica sol, xanthan gum, pure water and calcium aluminate cement, the silica sol accounts for 18% of the total weight of the dry main ingredient, the xanthan gum accounts for 1.8% of the total weight of the dry main ingredient, the pure water accounts for 5.45% of the total weight of the dry main ingredient, and the calcium aluminate cement accounts for 18.2% of the total weight of the dry main ingredient.
[0023] The silica sol density is 1.2 g / cm 3 .
[0024] The wollastonite, silica fume powder and quartz powder are 50 meshes, and their main function is to reduce thermal conductivity and improve the thermal shock resistance and anti-scouring ability of the product.
[0025] The calcined alumina is 3000 mesh.
[0026] The present invention also includes a method for producing a high-strength and high-toughness filter material, comprising the following steps:
[0027] Step 1, dry mixing: firstly, weighed quartz powder, wollastonite, silica fume powder, andalusite, calcium aluminate cement, explosion-proof fiber, calcined alumina, magnesium fluoride (cosolvent) and calcium aluminate cement are put into a mixing device 1, stirred and mixed to form a dry material;
[0028] Step 2, wet mixing: adding weighed silica sol, xanthan gum (thickener), and purified water into the mixing device 2, stirring and mixing to form a liquid material;
[0029] Step 3, add the liquid material in step 2 to the dry material in step 1 and stir to mix; stir evenly without lumps or powder, and control the on-site temperature at 15°C;
[0030] Step 4: Forming: Put the mixed materials in step 3 into the mold and vibrate to form a green body; specifically, pour the mixed materials into the mold and vibrate for 10-12 minutes. Inspection standard: Put the spherical clay in the palm of your hand and gently shake it into a cone, which is the ideal state;
[0031] Step 5, curing and firing: curing and firing the green body formed in step 4 to form a product;
[0032] Step six, testing: Randomly take three products from step five and conduct strength and non-stick aluminum performance tests. If the tests are qualified, the batch of products is qualified.
[0033] The stirring time in step 1 is 40 min, the stirring time in step 2 is 30 min, and the stirring time in step 3 is 10 min.
[0034] In the step five, the curing time is 12 hours, the curing temperature is 15°C, the firing temperature is 750°C, and the firing curve is: use 24 hours to increase the temperature from room temperature to 150°C and keep it for 10 hours, then use 30 hours to increase the temperature to 400°C and keep it for 10 hours, then use 20 hours to increase the temperature to 600°C and keep it for 10 hours, then use 15 hours to increase the temperature to 750°C and keep it for 8 hours, then use 15 hours to cool down to 600°C and keep it for 10 hours, then use 15 hours to cool down to 400°C and keep it for 10 hours, then use 15 hours to cool down to 200°C and keep it for 8 hours, then use 10 hours to cool down to 100°C, and finally naturally cool down to room temperature and take out of the furnace.
[0035] The various parameters of the high-strength and high-toughness filter material produced in this embodiment are as follows:
[0036] Product appearance: smooth and clean surface, without burrs, corrosion, etc.
[0037] Non-stick aluminum performance: After use, the aluminum sheet is easy to clean without falling off.
[0038] Service life: ≥100 castings
[0039] Bulk density: ≤2.1g / cm 3
[0040] Thermal conductivity: ≤0.5W / (m·K)
[0041] Heating line change rate: ≤0.13%
[0042] The high-strength and high-toughness filtering material of this embodiment is applied in the production process of deformed aluminum alloy melting and casting. Since this embodiment adopts reasonable raw material ratio, stirring method, pre-testing and analysis of formula performance, high-temperature sintering process and other production processes, its density is 2.1g / cm3. After the deformation aluminum alloy melting and casting production is completed, the aluminum skin is easy to clean and the lining does not fall off. Various physical performance indicators are reasonable, which improves the customer's use effect, reduces the company's production cost, and enhances the company's core competitiveness.
[0043] Example 2
[0044] A high-strength and high-toughness filter material comprises a dry main ingredient and a binder; the dry main ingredient comprises, by weight, 14 parts of quartz powder, 3 parts of silica fume powder, 17 parts of wollastonite, 3 parts of andalusite, 0.8 parts of explosion-proof fiber, 2.5 parts of calcined alumina, 1.2 parts of magnesium fluoride, and 13 parts of calcium aluminate cement; the binder comprises silica sol, xanthan gum, pure water and calcium aluminate cement, the silica sol accounts for 40% of the total weight of the dry main ingredient, the xanthan gum accounts for 6% of the total weight of the dry main ingredient, the pure water accounts for 8% of the total weight of the dry main ingredient, and the calcium aluminate cement accounts for 20% of the total weight of the dry main ingredient.
[0045] The silica sol density is 1.2 g / cm 3 .
[0046] The wollastonite, silica fume powder and quartz powder are 100 meshes, and their main function is to reduce thermal conductivity and improve the thermal shock resistance and anti-scouring ability of the product.
[0047] The calcined alumina is 3500 mesh.
[0048] This embodiment also includes a method for producing a high-strength and high-toughness filter material, comprising the following steps:
[0049] Step 1, dry mixing: firstly, weighed quartz powder, wollastonite, silica fume powder, andalusite, calcium aluminate cement, explosion-proof fiber, calcined alumina, magnesium fluoride (cosolvent) and calcium aluminate cement are put into a mixing device 1, stirred and mixed to form a dry material;
[0050] Step 2, wet mixing: adding weighed silica sol, xanthan gum (thickener), and purified water into the mixing device 2, stirring and mixing to form a liquid material;
[0051] Step 3, add the liquid material in step 2 to the dry material in step 1 and stir to mix; stir evenly without lumps or powder, and control the on-site temperature at 28°C;
[0052] Step 4: Forming: Put the mixed materials in step 3 into the mold and vibrate to form a green body; specifically, pour the mixed materials into the mold and vibrate for 10-12 minutes. Inspection standard: Put the spherical clay in the palm of your hand and gently shake it into a cone, which is the ideal state;
[0053] Step 5, curing and firing: curing and firing the green body formed in step 4 to form a product;
[0054] Step six, testing: Randomly take three products from step five and conduct strength and non-stick aluminum performance tests. If the tests are qualified, the batch of products is qualified.
[0055] The stirring time in step 1 is 50 min, the stirring time in step 2 is 35 min, and the stirring time in step 3 is 11 min.
[0056] In the step five, the curing time is 12 hours, the curing temperature is 25°C, the firing temperature is 750°C, and the firing curve is: use 24 hours to increase the temperature from room temperature to 150°C and keep it for 10 hours, then use 30 hours to increase the temperature to 400°C and keep it for 10 hours, then use 20 hours to increase the temperature to 600°C and keep it for 10 hours, then use 15 hours to increase the temperature to 750°C and keep it for 8 hours, then use 15 hours to cool down to 600°C and keep it for 10 hours, then use 15 hours to cool down to 400°C and keep it for 10 hours, then use 15 hours to cool down to 200°C and keep it for 8 hours, then use 10 hours to cool down to 100°C, and finally naturally cool down to room temperature and take out of the furnace.
[0057] The various parameters of the high-strength and high-toughness filter material produced in this embodiment are as follows:
[0058] Product appearance: smooth and clean surface, without burrs, corrosion, etc.
[0059] Non-stick aluminum performance: After use, the aluminum sheet is easy to clean without falling off.
[0060] Service life: ≥100 castings
[0061] Bulk density: ≤2.1g / cm 3
[0062] Thermal conductivity: ≤0.5W / (m·K)
[0063] Heating line change rate: ≤0.13%
[0064] The high-strength and high-toughness filtering material of this embodiment is applied in the production process of deformed aluminum alloy melting and casting. Since this embodiment adopts reasonable raw material ratio, stirring method, pre-testing and analysis of formula performance, high-temperature sintering process and other production processes, its density is 2.1g / cm3. After the deformation aluminum alloy melting and casting production is completed, the aluminum skin is easy to clean and the lining does not fall off. Various physical performance indicators are reasonable, which improves the customer's use effect, reduces the company's production cost, and enhances the company's core competitiveness.
[0065] Example 3
[0066] A high-strength and high-toughness filter material comprises a dry main ingredient and a binder; the dry main ingredient comprises, by weight, 18 parts of quartz powder, 5 parts of silica fume powder, 20 parts of wollastonite, 4 parts of andalusite, 1 part of explosion-proof fiber, 5 parts of calcined alumina, 2 parts of magnesium fluoride, and 15 parts of calcium aluminate cement; the binder comprises silica sol, xanthan gum, pure water and calcium aluminate cement, the silica sol accounts for 55% of the total weight of the dry main ingredient, the xanthan gum accounts for 8.75% of the total weight of the dry main ingredient, the pure water accounts for 11.25% of the total weight of the dry main ingredient, and the calcium aluminate cement accounts for 22% of the total weight of the dry main ingredient.
[0067] The silica sol density is 1.2 g / cm 3 .
[0068] The wollastonite, silica fume powder and quartz powder are 140 meshes, and their main function is to reduce thermal conductivity and improve the thermal shock resistance and anti-scouring ability of the product.
[0069] The calcined alumina is 4000 mesh.
[0070] This embodiment also includes a method for producing a high-strength and high-toughness filter material, comprising the following steps:
[0071] Step 1, dry mixing: firstly, weighed quartz powder, wollastonite, silica fume powder, andalusite, calcium aluminate cement, explosion-proof fiber, calcined alumina, magnesium fluoride (cosolvent) and calcium aluminate cement are put into a mixing device 1, stirred and mixed to form a dry material;
[0072] Step 2, wet mixing: adding weighed silica sol, xanthan gum (thickener), and purified water into the mixing device 2, stirring and mixing to form a liquid material;
[0073] Step 3, add the liquid material in step 2 to the dry material in step 1 and stir to mix; stir evenly without lumps or powder, and control the on-site temperature at 35°C;
[0074] Step 4: Forming: Put the mixed materials in step 3 into the mold and vibrate to form a green body; specifically, pour the mixed materials into the mold and vibrate for 10-12 minutes. Inspection standard: Put the spherical clay in the palm of your hand and gently shake it into a cone, which is the ideal state;
[0075] Step 5, curing and firing: curing and firing the green body formed in step 4 to form a product;
[0076] Step six, testing: Randomly take three products from step five and conduct strength and non-stick aluminum performance tests. If the tests are qualified, the batch of products is qualified.
[0077] The stirring time in step 1 is 60 min, the stirring time in step 2 is 40 min, and the stirring time in step 3 is 12 min.
[0078] In the step five, the curing time is 12 hours, the curing temperature is 35°C, the firing temperature is 750°C, and the firing curve is: use 24 hours to increase the temperature from room temperature to 150°C and keep it for 10 hours, then use 30 hours to increase the temperature to 400°C and keep it for 10 hours, then use 20 hours to increase the temperature to 600°C and keep it for 10 hours, then use 15 hours to increase the temperature to 750°C and keep it for 8 hours, then use 15 hours to cool down to 600°C and keep it for 10 hours, then use 15 hours to cool down to 400°C and keep it for 10 hours, then use 15 hours to cool down to 200°C and keep it for 8 hours, then use 10 hours to cool down to 100°C, and finally naturally cool down to room temperature and take out of the furnace.
[0079] The various parameters of the high-strength and high-toughness filter material produced in this embodiment are as follows:
[0080] Product appearance: smooth and clean surface, without burrs, corrosion, etc.
[0081] Non-stick aluminum performance: After use, the aluminum sheet is easy to clean without falling off.
[0082] Service life: ≥100 castings
[0083] Bulk density: ≤2.1g / cm 3
[0084] Thermal conductivity: ≤0.5W / (m·K)
[0085] Heating line change rate: ≤0.13%
[0086] The high-strength and high-toughness filtering material of this embodiment is applied in the production process of deformed aluminum alloy melting and casting. Since this embodiment adopts reasonable raw material ratio, stirring method, pre-testing and analysis of formula performance, high-temperature sintering process and other production processes, its density is 2.1g / cm3. After the deformation aluminum alloy melting and casting production is completed, the aluminum skin is easy to clean and the lining does not fall off. Various physical performance indicators are reasonable, which improves the customer's use effect, reduces the company's production cost, and enhances the company's core competitiveness.
[0087] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A high-strength and high-toughness filter material, comprising a dry main material and a binder; characterized in that: The dry main ingredients include 10-18 parts of quartz powder, 1-5 parts of silica fume powder, 12-20 parts of wollastonite, 1-4 parts of andalusite, 0.3-1 parts of explosion-proof fiber, 1-5 parts of calcined alumina, 0.5-2 parts of magnesium fluoride, and 10-15 parts of calcium aluminate cement by weight; the binder includes silica sol, xanthan gum, pure water and calcium aluminate cement, the silica sol accounts for 18-55% of the total weight of the dry main ingredients, the xanthan gum accounts for 1.8-8.75% of the total weight of the dry main ingredients, the pure water accounts for 5.45-11.25% of the total weight of the dry main ingredients, and the calcium aluminate cement accounts for 18.2-22% of the total weight of the dry main ingredients.
2. The high-strength and high-toughness filter material according to claim 1, characterized in that: The silica sol density is 1.2 g / cm 3 .
3. The high-strength and high-toughness filter material according to claim 1, characterized in that: The wollastonite, silica fume powder and quartz powder are 50-140 mesh.
4. The high-strength and high-toughness filter material according to claim 1, characterized in that: The calcined alumina has a mesh size of 3000-4000.
5. A method for producing a high-strength and high-toughness filter material according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, dry mixing: firstly, weighed quartz powder, wollastonite, silica fume powder, andalusite, calcium aluminate cement, explosion-proof fiber, calcined alumina, magnesium fluoride and calcium aluminate cement are put into a mixing device 1, stirred and mixed to form a dry material; Step 2, wet mixing: adding weighed silica sol, xanthan gum, and purified water into the mixing device 2, stirring and mixing to form a liquid material; Step 3, adding the liquid material in step 2 to the dry material in step 1 and stirring to mix; Step 4: Forming: Put the mixed material in step 3 into a mold and vibrate to form a green body; Step 5, curing and firing: curing and firing the green body formed in step 4 to form a product; Step six, testing: Randomly take three products from step five for strength and non-stick aluminum performance testing. If the test is qualified, the batch of products is qualified.
6. The method for producing a high-strength and high-toughness filter material according to claim 5, characterized in that: The stirring time in step 1 is 40-60 min, the stirring time in step 2 is 30-40 min, and the stirring time in step 3 is 10-12 min.
7. The method for producing a high-strength and high-toughness filter material according to claim 6, characterized in that: In the step 5, the curing time is 72 hours, the curing temperature is 15-35°C, and the firing temperature is 750°C.
Citation Information
Patent Citations
Novel refractory material for aluminum smelting industry and preparation method of novel refractory material
CN103204688A
Light non-stick aluminum material and production method thereof
CN112279661A
Refractory compositions
WO2008060161A1
